Imagining liberation: a prophetic literary analysis in Atef Abu Saif’s diary “don’t look left: a diary of genocide” - Andriani, Zulfi Zumala Dwi (UNIB Press, 2025)
This article examines the quest for liberation by Palestinians amidst Israel's assault on the Gaza Strip from October 2023 to December 2023, as documented in Atef Abu Saif's diary,